Refugees, nationalism, and political membership - Signe Larsen (Nordicum-Mediterraneum, 2012)
This essay aims to understand how refugees present a problem for liberal nation-states. The point of departure is Arendt’s The Origins of Totalitarianism where she argues that the continual existence of refugees within liberal nation-states threatens to break down the principle of equality before the law thereby enabling the rise of police-states and totalitarianism. In light of this diagnosis, three of Arendt’s philosophical heirs—Giorgio Agamben, Seyla Benhabib and Peg Birmingham—argue that it is necessary to think political membership in different and broader terms than national citizenship if we are to avoid a new rise of totalitarianism.